High power Stirling Engine with low temperature difference for education using 3D printers - Takashi FUKUI (Nihon Kikai Gakkai ronbunshu, 2024)
Low temperature difference Stirling engine is an excellent teaching material for mechanical design because (1) students can experience all of four dynamics (material mechanics, fluid dynamics, thermodynamics, and dynamics of machinery) by designing and constructing it, (2) it is safe even if the design is not appropriate, so it allows students to freely try their own ideas, (3) there are many variations of engine configurations, including types and mechanisms, so there is much room for creativity and ingenuity, and (4) as the structure is simple, it is easy for students to understand if their ideas make sense. On the other hand, it is not easy to construct a working engine because of its low power. In order to make low temperature difference Stirling engines more effective teaching materials, this paper describes the design and fabrication of a low temperature difference Stirling engine with high power per swept volume that can run at higher speed. The results of analyzing the working fluid temperatures in the expansion and compression spaces indicate that the temperature ratio increases with increasing speed even in a low temperature difference Stirling engine. We found that an arrayed resin regenerator can provide high performance, and realized that a Stirling engine with a power piston swept volume of 4.5 cc and using hot water and ice as heat sources can run at a maximum power of 171 mW and a maximum speed of 31.3 Hz. Compared with other low temperature difference Stirling engines, the power per swept volume of test engine is more than 10 times higher and the rotational speed is nearly three times higher than those of the low temperature difference Stirling engines already reported. The results show that low temperature difference Stirling engines with high power per swept volume can be designed and fabricated by using 3D printers, and the value of the low temperature difference Stirling engine as a teaching material has been enhanced.